2020
DOI: 10.1159/000505329
|View full text |Cite
|
Sign up to set email alerts
|

Management of Systemic Hypersensitivity Reactions to Gonadotropin-Releasing Hormone Analogues during Treatment of Central Precocious Puberty

Abstract: Besides local reactions, systemic hypersensitivity reactions such as urticaria, anaphylaxis, serum sickness and Henoch-Schönlein purpura (HSP) have been reported during gonadotropin-releasing hormone (GnRH) analogue treatment. Novel Insights• We present 9 cases with systemic hypersensitivity reactions to GnRH analogue and discussed the management approaches based on our experience. AbstractBackground: Besides local reactions, systemic hypersensitivity reactions such as urticaria, anaphylaxis, serum sickness an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Kirkgoz et al ( 22 ) recently reported nine pediatric cases experienced systemic hypersensitivity reactions to GnRHa during the treatment of CPP. One of the cases in this report had similarities to the currently presented case with palpable purpuric rash on her legs, which was assumed to be Henoch-Schönlein purpura by her pediatrician.…”
Section: Discussionmentioning
confidence: 99%
“…Kirkgoz et al ( 22 ) recently reported nine pediatric cases experienced systemic hypersensitivity reactions to GnRHa during the treatment of CPP. One of the cases in this report had similarities to the currently presented case with palpable purpuric rash on her legs, which was assumed to be Henoch-Schönlein purpura by her pediatrician.…”
Section: Discussionmentioning
confidence: 99%
“…Puberty is a transition period from childhood to adulthood with a gradual maturation of the sexual and reproductive systems. Children with central precocious puberty (CPP) show an advanced initiation of hypothalamus-pituitary-gonadal (HPG) axis function, which leads to a rapid development of internal and external reproductive organs and secondary sexual sign before the age of 8 in girls and the age of 9 in boys (Leger, 2002;Kirkgoz et al, 2020). The incidence of CPP is about 1/5,000-10,000, accounting for more than 30% of the total number of pediatric endocrine outpatients (Abreu et al, 2015;Li C. Y. et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…There are differences in additives or stabilizing agents in GnRHa that may be causing hypersensitivity reactions. [ 8 ] In the patient who had reactions to both GnRHa, reactions to additives should be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Due to cases that were shown cross-reactivity between two different GnRHa, before switching the medication to the other analogs, skin tests with alternative medications should be done. [ 8 9 ] Since depot forms of GnRH analogs contain more content than the active drug, it should be kept in mind that such commercial preparations may be exceeding the concentration of irritants on the skin for IDT and SPT. This problem causes difficulty in evaluating tests and a lack of data in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation